Anti-cracking high-pressure steam-curing-free tubular pile concrete and preparation method thereof
By using polyether modified silicone oil and amino-polyethylene glycol-maleimide as defoaming agent in PHC pipe pile concrete, the pores and weakness caused by the introduction of air bubbles in concrete in the prior art are solved. Interface problems achieve high compressive strength and excellent split tensile performance after freeze-thaw cycle.
Patent Information
- Application Number
- CN202411709932.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-21
AI Technical Summary
The existing PHC pipe pile concrete is prone to introduce bubbles during the mixing and pouring process, resulting in excessive pores and weak interfaces in the cured concrete, which affects its cracking resistance and the tensile strength of the splitting after freeze-thaw cycle.
The composite of polyether modified silicone oil and amino-polyethylene glycol-maleimide is used as the defoaming agent. By reasonably controlling the pore volume and pore structure in concrete, the stress concentration is reduced, the compressive strength is improved, and Accept excess free water during freeze-thaw cycle to avoid microcracks in the pore wall.
The rationality of the pore volume and pore structure in the concrete is achieved, the compressive strength and the split tensile strength after freeze-thaw cycle are improved, the loss of split tensile strength is reduced, and the overall safety and reliability of the concrete are enhanced.
Smart Images

Figure BDA0005155414960000041 
Figure BDA0005155414960000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials, and in particular relates to anti-cracking high-pressure steam curing-free pipe pile concrete and a preparation method thereof. Background Art
[0002] Prestressed high-strength concrete pipe piles (PHC pipe piles for short) are hollow cylindrical concrete components made using prestressing, centrifugal forming, steam curing and pressure steam curing processes. Compared with other engineering infrastructure materials, PHC pipe piles have the advantages of short construction period, excellent mechanical properties, high cost performance, and few restrictions on construction conditions. They are widely used in the construction industry.
[0003] As the pipe pile industry continues to develop and mature, the shrinking profit margin requires pipe pile manufacturers to find new breakthroughs, improve the quality of pipe piles, and reduce the cost of pipe piles in order to win the market. Researchers have found that silica sand powder, slag powder, fly ash and other admixtures can significantly reduce the amount of cement, saving the cost of raw materials in pipe pile production. The pressure steam curing conditions will also promote the hydration reaction of silica sand powder, slag powder, fly ash and other admixtures and increase the crystal-gel ratio, which not only brings huge economic benefits, but also cooperates with cement to form a dense concrete structure, giving pipe pile concrete excellent anti-permeability properties. Therefore, it has been promoted in the PHC pipe pile industry. For example, patent CN1291110C discloses a concrete pipe pile mixed with ground slag powder and a production method thereof. A concrete pipe pile mixed with ground slag powder comprises concrete, and the specific mix ratio (parts by weight) is: 1 cement, 1.5-2.9 yellow sand, 3.2-5.0 crushed stone, 0.3-0.6 water, 0.025-0.045 water reducer, and 0.2-1 ground slag powder. Patent CN114804781B discloses a durable PHC pipe pile concrete and a PHC pipe pile. The durable PHC pipe pile concrete comprises the following components: 340-470 parts of cement, 30-50 parts of waterproof particles, 780-1300 parts of aggregate, 25-60 parts of mineral powder, 25-60 parts of fly ash, 3-5 parts of water reducer, and 68-94 parts of water; the waterproof particles comprise VAE emulsion, acrylic emulsion, and stone powder in a weight ratio of 1:(2-5):(15-22); the preparation method thereof comprises: preparing the waterproof particles, premixing, and mixing; the preparation method of the PHC pipe pile made with the durable PHC pipe pile concrete comprises: cleaning the mold, spraying a release agent, making a steel cage skeleton and a pipe pile joint, installing the mold, grouting, closing the mold, tensioning, centrifuging, autoclaving, and demolding.
[0004] Because silica sand powder, slag powder, fly ash and other admixtures have large specific surface area, small particle size, strong water absorption capacity, and the presence of surfactants such as water reducers, bubbles are easily introduced into the concrete system during mixing and pouring. After the bubbles come into contact with large solid particles such as cement, the bubble liquid film becomes thicker and the elasticity increases, and they can stably exist in the concrete. Some bubbles will be discharged through vibration and centrifugation, but due to the obstruction of small-particle admixtures, most bubbles still exist in the system, resulting in too many pores and weak interfaces in the cured concrete. Although the effect on compressive strength is not obvious, the expansion and extension of microcracks during the splitting test are carried out along the weak interface, which has a significant impact on the splitting tensile strength of the pipe pile concrete and the splitting tensile strength after freeze-thaw cycles, thereby affecting the overall safety and reliability of the concrete structure. Therefore, it is necessary to develop a pipe pile concrete with excellent crack resistance. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a crack-resistant high-pressure steam-curing-free pipe pile concrete and a preparation method thereof, wherein a compound of polyether-modified silicone oil and amino-polyethylene glycol-maleimide is used as a defoaming agent to make the pore amount and pore structure in the concrete reasonable, without a weak interface caused by too many pores, and with pores with a reasonable number and distribution to reduce stress concentration in the concrete, improve compressive strength, and accommodate excess free water generated during freeze-thaw cycles without causing microcracks in the pore wall and reducing the splitting tensile strength.
[0006] In order to achieve the above purpose, the following technical solutions are adopted:
[0007] A crack-resistant, autoclave-free pipe pile concrete comprises the following raw materials in parts by weight: 1000 parts of cement, 2100-2500 parts of fine aggregate, 3570-4250 parts of coarse aggregate, 250-330 parts of admixture, 25-45 parts of high-efficiency water reducing agent, 10-30 parts of early strength agent, 5-8 parts of defoaming agent, and 300-350 parts of water, wherein the defoaming agent is compounded by polyether-modified silicone oil and amino-polyethylene glycol-maleimide in a mass ratio of 1-3:1, and the early strength agent is compounded by triethanolamine and phytic acid in a mass ratio of 10:1-2.
[0008] The polyether modified silicone oil has a viscosity of 500-1500 cst at 25° C. and a surface tension of 20-23 mN / m.
[0009] The weight average molecular weight of the amino-polyethylene glycol-maleimide is 600-1000 mol / g.
[0010] Polyether-modified silicone oil is made of a polyether-siloxane copolymer obtained by introducing a hydrophilic polyether segment into a hydrophobic silicone molecular chain. It has good anti-foaming and anti-foaming capabilities. Since it can self-emulsify in a water system, the defoaming effect is long-lasting. The inventor found that the use of polyether-modified silicone oil in combination with amino-polyethylene glycol-maleimide can give the pipe pile concrete excellent splitting tensile strength and splitting tensile strength after freeze-thaw cycles, but the compounding ratio of the two needs to be appropriately selected. When there is too much polyether-modified silicone oil, there are still a large number of weak interfaces, and the splitting tensile strength and splitting tensile strength after freeze-thaw cycles are still poor; when there is too little polyether-modified silicone oil, the compressive strength and splitting tensile strength after freeze-thaw cycles are low.
[0011] The possible reason is that maleimide groups can provide better rigidity and support than silicon oxygen bonds, making amino-polyethylene glycol-maleimide molecules more resistant to shear than polyether-modified silicone oils, and showing stronger defoaming ability during concrete mixing and shearing, when a large number of bubbles are generated. In order for the defoamer to show appropriate defoaming ability and durability of defoaming effect during mixing and later process operations, the amount of pores and pore distribution in concrete should be reasonable, without weak interfaces caused by too many pores, and with a reasonable number and distribution of pores to reduce stress concentration in concrete, improve compressive strength, and accommodate excess free water generated during freeze-thaw cycles without causing microcracks in the pore wall and reducing splitting tensile strength, it is necessary to adjust the ratio of polyether-modified silicone oil and amino-polyethylene glycol-maleimide.
[0012] The high-efficiency water reducer is selected from one or a combination of polycarboxylic acid high-efficiency water reducer and naphthalene-based high-efficiency water reducer.
[0013] The admixture is selected from one or a combination of two or more of fly ash, mineral powder, and silica sand powder.
[0014] Furthermore, the admixture is fly ash; the fly ash has a fineness of 20-25%, a water requirement ratio of 80-100%, and a 7-day activity index of not less than 85%.
[0015] The fine aggregate fineness modulus is 2.3-3.4.
[0016] The coarse aggregate is natural crushed stone with an average particle size of 5-25 mm.
[0017] The cement is silicate cement with a strength grade of 42.5-52.5.
[0018] The present invention also provides a method for preparing the above-mentioned high-pressure steam-curing-free pipe pile concrete, comprising the following steps:
[0019] Add cement, fine aggregate, coarse aggregate, admixture, high-efficiency water reducing agent, early strength agent, defoaming agent and water into a mixer and mix until uniform, thereby avoiding high-pressure steam-curing of pipe pile concrete.
[0020] Application of anti-cracking autoclave-free pipe pile concrete in the preparation of autoclave-free pipe piles.
[0021] Furthermore, the application comprises the following steps:
[0022] The non-autoclaved pipe pile concrete is injected into the pipe pile mold, the mold is closed, and the pipe pile mold after the mold is closed is subjected to prestressing tensioning treatment, centrifugal treatment, steam curing, demoulding, and natural curing to obtain the non-autoclaved pipe pile.
[0023] The steam curing is to raise the temperature to 80-90° C. within 1-3 hours and keep the temperature for 3-6 hours.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention adopts a compound of polyether modified silicone oil and amino-polyethylene glycol-maleimide as a defoamer, so that the pore amount and pore structure in the concrete are reasonable, there is no weak interface caused by too many pores, and the pores with a reasonable number and distribution reduce the stress concentration in the concrete, improve the compressive strength, and accommodate the excess free water generated during the freeze-thaw cycle without causing micro cracks in the pore wall and reducing the splitting tensile strength. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0027] The weight average molecular weight of amino-polyethylene glycol-maleimide is 600 mol / g and 1000 mol / g, both of which were purchased from Guangzhou Carbon Technology Co., Ltd.
[0028] Fly ash Fly ash was purchased from Hebei Wenfeng Industrial Group Co., Ltd. The fly ash fineness was 23.6%, the water requirement ratio was 98%, and the 7-day activity index was 95%.
[0029] The polyether modified silicone oil IOTA-1291 was purchased from Anhui IOTA Silicone Oil Co., Ltd., with a viscosity of 750 cst at 25°C and a surface tension of 23 mN / m at 25°C.
[0030] The polyether-modified silicone oil EASYTECH ST-1076 was purchased from Shanghai Sangjing Chemical Co., Ltd., with a viscosity of 870 cst at 25°C and a surface tension of 20.6 mN / m at 25°C.
[0031] PO42.5 silicate cement was purchased from Anhui Conch Cement Co., Ltd.
[0032] The high-efficiency water reducing agent was purchased from BASF, with the brand name Melflux 4930F.
[0033] The fine aggregate was purchased from Zhuzhou Aggregate New Material Co., Ltd. and was medium sand with a fineness modulus of 2.6.
[0034] The coarse aggregate was purchased from Zhuzhou Aggregate New Materials Co., Ltd. The screening results of 5-10mm and 10-20mm crushed stones showed that the mass ratio of 5-10mm to 10-20mm was 1:4:
[0035] Table 1 Crushed stone screening results
[0036]
[0037] Example 1
[0038] 1000g PO42.5 silicate cement, 2100g fine aggregate, 4250g coarse aggregate, 330g fly ash, 45g high-efficiency water reducing agent, 30g early strength agent prepared by compounding triethanolamine and phytic acid in a mass ratio of 10:1, 8g defoaming agent prepared by compounding polyether modified silicone oil IOTA-1291 and amino-polyethylene glycol-maleimide with a weight average molecular weight of 600mol / g in a mass ratio of 1:1, and 350g water are added into a mixer and stirred until uniform to obtain autoclave-free pipe pile concrete.
[0039] The autoclave-free pipe pile concrete is injected into the pipe pile mold, the mold is closed, and the mold after closing is subjected to prestressing tensioning treatment, the pipe pile mold is subjected to centrifugal treatment, the temperature is raised to 80°C within 2 hours, steam-cured and kept warm for 6 hours, demolded, and naturally cured to obtain the autoclave-free pipe pile.
[0040] The centrifugal treatment includes: a low speed stage of centrifuging at a speed of 60 r / min for 2 min, a low-medium speed stage of centrifuging at a speed of 115 r / min for 2 min, a medium speed stage of centrifuging at a speed of 290 r / min for 4 min, and finally a high speed stage of centrifuging at a speed of 480 r / min for 7 min.
[0041] Example 2
[0042] The rest is the same as Example 1, except that the weight average molecular weight of amino-polyethylene glycol-maleimide is 1000 mol / g.
[0043] Example 3
[0044] The rest is the same as Example 1, except that the polyether-modified silicone oil EASYTECH ST-1076 of equal mass is used to replace the polyether-modified silicone oil IOTA-1291.
[0045] Example 4
[0046] The rest is the same as Example 1, except that the defoaming agent is compounded by polyether-modified silicone oil IOTA-1291 and amino-polyethylene glycol-maleimide with a weight average molecular weight of 600 mol / g in a mass ratio of 3:1.
[0047] Example 5
[0048] The rest is the same as Example 1, except that the amount of the defoaming agent is 5 g.
[0049] Example 6
[0050] The rest is the same as Example 1, except that the early strength agent is compounded by triethanolamine and phytic acid in a mass ratio of 10:2.
[0051] Example 7
[0052] The rest is the same as Example 1, except that the dosage of the early strength agent is 10 g.
[0053] Example 8
[0054] The rest is the same as Example 1, except that 1000g PO42.5 silicate cement, 2500g fine aggregate, 4250g coarse aggregate, 2500g fly ash, 45g high-efficiency water reducer, 10g early strength agent prepared by compounding triethanolamine and phytic acid in a mass ratio of 10:2, 8g defoaming agent prepared by compounding polyether modified silicone oil IOTA-1291 and amino-polyethylene glycol-maleimide with a weight average molecular weight of 600mol / g in a mass ratio of 1:1, and 350g water are added to a mixer and stirred until uniform to obtain high-pressure steam-cured pipe pile concrete.
[0055] Comparative Example 1
[0056] The rest is the same as Example 1, except that the early strength agent is all triethanolamine.
[0057] Comparative Example 2
[0058] The rest is the same as Example 1, except that the early strength agent is all phytic acid.
[0059] Comparative Example 3
[0060] The rest is the same as Example 1, except that the defoaming agent is compounded by polyether-modified silicone oil IOTA-1291 and amino-polyethylene glycol-maleimide with a weight average molecular weight of 600 mol / g in a mass ratio of 4:1.
[0061] Comparative Example 4
[0062] The rest is the same as Example 1, except that the defoaming agent is compounded by polyether-modified silicone oil IOTA-1291 and amino-polyethylene glycol-maleimide with a weight average molecular weight of 600 mol / g in a mass ratio of 0.5:1.
[0063] The pipe pile concrete prepared in the above embodiments and comparative examples was subjected to the following performance tests:
[0064] Compressive strength: 1d and 28d strength tests were carried out with reference to the standard GB / T50081-2019 Test method for physical and mechanical properties of concrete. The samples were prepared by drilling standard cubic specimens with a side length of 150mm on the surface of the pipe piles in the above-mentioned embodiments and comparative examples. Three pieces of each sample were prepared, and the average value of the three pieces was taken.
[0065] Splitting tensile strength: Tested in accordance with GB / T 50081-2019 Test method for physical and mechanical properties of concrete.
[0066] Anti-freeze performance test: refer to the standard GB / T 50082-2009 Test method for long-term performance and durability of ordinary concrete, -20℃ / 4h and 18℃ / 4h as one cycle, and freeze-thaw cycles are performed 300 times for the specimens with an age of 28d. The splitting tensile strength is retested and the splitting tensile strength loss rate is calculated.
[0067] The test results are shown in Table 2 below.
[0068] Table 2 Test results
[0069]
[0070] It can be seen from Example 1 and Comparative Examples 1-4 that the amino-polyethylene glycol-maleimide in the early strength agent and the defoamer has an obvious synergistic effect of improving the later compressive strength, so that the preparation of the pipe pile containing the admixture can be achieved without autoclaving.
[0071] It can be seen from Table 2 that the pipe pile concrete prepared by the present invention has excellent compressive strength, and the splitting tensile strength before and after freeze-thaw cycles is relatively high.
[0072] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A crack-resistant, autoclave-free pipe pile concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 1000 parts of cement, 2100-2500 parts of fine aggregate, 3570-4250 parts of coarse aggregate, 250-330 parts of admixture, 25-45 parts of high-efficiency water reducing agent, 10-30 parts of early strength agent, 5-8 parts of defoaming agent and 300-350 parts of water, wherein the defoaming agent is compounded by polyether modified silicone oil and amino-polyethylene glycol-maleimide in a mass ratio of 1-3:1, and the early strength agent is compounded by triethanolamine and phytic acid in a mass ratio of 10:1-2.
2. The anti-cracking autoclave-free pipe pile concrete according to claim 1, characterized in that: The polyether modified silicone oil has a viscosity of 500-1500 cst at 25° C. and a surface tension of 20-23 mN / m.
3. The anti-cracking autoclave-free pipe pile concrete according to claim 1, characterized in that: The weight average molecular weight of the amino-polyethylene glycol-maleimide is 600-1000 mol / g.
4. The anti-cracking autoclave-free pipe pile concrete according to claim 1, characterized in that: The high-efficiency water reducer is selected from one or a combination of polycarboxylic acid high-efficiency water reducer and naphthalene-based high-efficiency water reducer.
5. The anti-cracking autoclave-free pipe pile concrete according to claim 1, characterized in that: The admixture is selected from one or a combination of two or more of fly ash, mineral powder, and silica sand powder.
6. The anti-cracking autoclave-free pipe pile concrete according to claim 5, characterized in that: The admixture is fly ash with a fineness of 20-25%, a water requirement ratio of 80-100%, and a 7-day activity index of not less than 85%.
7. The method for preparing the autoclave-free pipe pile concrete according to any one of claims 1 to 6, characterized in that: The steps include: Add cement, fine aggregate, coarse aggregate, admixture, high-efficiency water reducing agent, early strength agent, defoaming agent and water into a mixer and mix until uniform, thereby avoiding high-pressure steam-curing of pipe pile concrete.
8. Use of the anti-cracking autoclave-free pipe pile concrete according to any one of claims 1 to 6 or claim 7 in the preparation of autoclave-free pipe piles.
9. The use of the anti-cracking autoclave-free pipe pile concrete according to claim 8 in the preparation of autoclave-free pipe piles, characterized in that: The application comprises the following steps: The non-autoclaved pipe pile concrete is injected into the pipe pile mold, the mold is closed, and the pipe pile mold after the mold is closed is subjected to prestressing tensioning treatment, centrifugal treatment, steam curing, demoulding, and natural curing to obtain the non-autoclaved pipe pile.
10. The use of the anti-cracking autoclave-free pipe pile concrete according to claim 9 in the preparation of autoclave-free pipe piles, characterized in that: The steam curing is to raise the temperature to 80-90° C. within 1-3 hours and keep the temperature for 3-6 hours.
Citation Information
Patent Citations
Durable PHC pipe pile concrete and PHC pipe pile
CN114804781B
Concrete tube pile with fine milled slag micropowder and production me thod thereof
CN1291110C